1999
DOI: 10.1016/s0035-9203(99)90341-3
|View full text |Cite
|
Sign up to set email alerts
|

Permethrin-treated chaddars and top-sheets: appropriate technology for protection against malaria in Afghanistan and other complex emergencies

Abstract: Insecticide-treated mosquito nets (ITN) provide excellent protection against malaria; however, they have a number of shortcomings that are particularly evident in politically unstable countries or countries at war: not everyone at risk can necessarily afford a net, nets may be difficult to obtain or import, nets may not be suitable for migrants or refugees sleeping under tents or plastic shelter. There is a need to develop cheaper, locally appropriate alternatives for the most impoverished and for victims of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 19 publications
4
87
1
Order By: Relevance
“…In field studies, selfimpregnation of clothing with permethrin was protective against disease in short-term studies, [10][11][12] but not in long term. 13 LLPI clothing has been previously shown to be effective in laboratory settings 5 and to retain mosquito knockdown efficacy for up to 20 washes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In field studies, selfimpregnation of clothing with permethrin was protective against disease in short-term studies, [10][11][12] but not in long term. 13 LLPI clothing has been previously shown to be effective in laboratory settings 5 and to retain mosquito knockdown efficacy for up to 20 washes.…”
Section: Discussionmentioning
confidence: 99%
“…In one large study, impregnated clothing, sheets, and other materials protected against malaria when used for 16 weeks. 10 Two other smaller short-term studies were done-one showed an effect 11 and one did not. 12 Finally, in the only long-term study (13 months), no effect on the incidence of infection was seen.…”
Section: Introductionmentioning
confidence: 99%
“…23 In Afghanistan, permethrin-treated Islamic cloth wraps (chaddars) used to sleep in and top-sheets reduced the odds of an episode of malaria by 64% in children younger than 10 years, at a cost of US$ 0.17 per person protected. 24 Deltamethrin-treated plastic tarpaulins in Afghan refugee camps effectively killed mosquitoes for prolonged periods. 25 …”
Section: Policy and Practice Child Health In Complex Emergenciesmentioning
confidence: 99%
“…In areas of a low, unstable intensity of transmission, people of all ages are affected, but malaria is a particular problem in those who are exposed to the disease because of their occupations. Interventions that have been proposed to reduce the risk of malaria in these high-risk groups include impregnated nets (7), hammocks (13), and other materials (2,3,8); insect repellents (9); and continuous antimalarial chemoprophylaxis. An alternative approach, developed originally for pregnant women in areas of high intensity of stable transmission, is the administration of an antimalarial treatment dose at regular intervals to exposed individuals, irrespective of parasitemia.…”
mentioning
confidence: 99%